PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2014 - Ahmad Jairil Haris; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study was conducted to examine the effect of working capital management to company profitability Food and Beverage listed on the Indonesia Stock Exchange. Ie working capital management as indicated by Turnover Cash, Accounts Receivable Turnover and Inventory Turnover With Profitability as indicated by Return On Investment (ROI).The data used in this research is secondary data. The study population was firm Food and Beverage Industrylisted on the Indonesia Stock Exchange during the period 2009-2014. The sampling method used is purposive sampling as many as six companies during the six years of observation in order to get as much data as the company's financial statements 36 food and beverage industry listed in Indonesia Stock Exchange 2009-2014 period. Classic assumption test in this study include normality test, multikoliniearitas, heterocedasticity test, test autokolerasi. Analisisis data analysis using multiple linear regression, t-test, f and the coefficient of determination test. Analysis of data using multiple linear regression analysis with SPSS 16.The analysis showed that the variables of cash and accounts receivable turnover perputaraan partially (t test) significant negative effect on ROI while variable inventory turnover no significant effect on ROI. Results simultaneous (f test) shows that all independent variables significant positive effect on ROI. Adjusted R squre of 0.350 indicating that 35.0% ROI can be explained by the independent variable cash turnover, accounts receivable turnover and inventory turnover. While the rest of 65.0% is explained by other variables.Keywords : Turnover Cash, Accounts Receivable Turnover, Inventory Turnover, Profitability (ROI).